Crystallization Morphology and Self-Assembly of Polyacrylamide Solutions During Evaporation - Hu, Jun; Wang, Zhan-Long (Fine Chemical Engineering, 2024)
This study investigates the crystallization and self-assembly phenomena of polyacrylamide (PAM) solutions during evaporation. While traditional thin-film fabrication methods such as spin coating and drop casting are commonly used, this study utilizes a simple evaporation approach to gain insights into the self-assembly processes of PAM solutions. We examined PAM solutions with varying concentrations (1%, 2%, and 5%) and observed the resulting crystalline structures and morphological changes during evaporation. Spectroscopic absorbance measurements were employed to analyze concentration gradients and crystallization patterns. The findings reveal that the concentration gradient during evaporation significantly impacts the crystallization behavior of PAM solutions. The 2% solution exhibited the clearest and most regular crystalline patterns, whereas the 1% and 5% solutions displayed more complex and irregular morphologies. These observations provide new insights into how solution concentration influences PAM crystallization, contributing to a better understanding of polymer thin-film self-assembly. The novelty of this study lies in exploring PAM self-assembly through controlled evaporation, offering valuable insights for the development of polymer films.